2020
DOI: 10.1186/s12978-020-00962-3
|View full text |Cite
|
Sign up to set email alerts
|

Unmet family planning needs among female refugees and asylum seekers in Germany – is free access to family planning services enough? Results of a cross-sectional study

Abstract: Background: After the 1968 United Nations International Conference on Human Rights, access to family planning services became a human right. Such a service is of central importance to women's empowerment and is empirically needed to provide adequate healthcare. For registered refugees and asylum seekers in Germany complementary family planning services, including all forms of contraception, are free of charge. Yet, the success of these services remains unclear. The aim of this study is to describe the current … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…According to the United Nations Population Fund (UNFPA), one billion people – one in every seven – are migrants. 1 , 2 About 250 million people are international migrants, and nearly half of them are women. 1 Globally, women are migrating to new countries, bringing with them their perspectives and knowledge about sexual and reproductive health and rights (SRHR) and contraceptives.…”
Section: Introductionmentioning
confidence: 99%
“…According to the United Nations Population Fund (UNFPA), one billion people – one in every seven – are migrants. 1 , 2 About 250 million people are international migrants, and nearly half of them are women. 1 Globally, women are migrating to new countries, bringing with them their perspectives and knowledge about sexual and reproductive health and rights (SRHR) and contraceptives.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by our working group showed, in addition, that only 53 % of refugee women who wished to avoid pregnancy used contraceptive methods. 34 % of them used the unreliable method of coitus interruptus [12]. This could help to explain the younger maternal age and the frequent pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Eine andere Studie unserer Arbeitsgruppe hat zudem gezeigt, dass nur 53 % der geflüchteten Frauen, die sich keine Schwangerschaft wünschten, kontrazeptive Methoden verwendeten. 34 % davon verhüteten mit der unsicheren Methode des Coitus interruptus [12]. Das könnte ein Erklärungsansatz für das jüngere maternale Alter sowie für die häufigen Schwangerschaften sein.…”
Section: Diskussionunclassified
“…The relatively high birthrate among asylum seekers in this study was likely related to limited access to and availability of sexual and reproductive health services throughout the process of forced migration [ 24 , 25 , 26 , 27 ]. In absolute numbers, most children in this study were born to mothers from the Middle East/North Africa, a region which includes common countries of origin among asylum seekers such as Syria and Iraq [ 28 ].…”
Section: Discussionmentioning
confidence: 99%